“PUPOS (PUPUK KOMPOS)” COMMUNITY EMPOWERMENT TO PROCESS AND RECYCLE HOUSEHOLD WASTE EASILY AND QUICKLY - Delyana Rahmawany Pulungan; Dina Arfianti Saragih; Tifany Zia Aznur; Purjianto; Rina Maharany; Ritna Wahyuni (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Waste is a problem in various big cities, one of which is Medan City. Organic waste that is wet and causes foul odor needs to be dealt with quickly. One method of managing organic waste is by processing it into compost. Compost made from organic waste is very easy because it does not require a large area, a lot of equipment and costs. This community service activity aims to empower housewives through education and composting trials as an independent alternative for them to overcome household waste that can be used to make organic fertilizer that can be used alone or sold for a source of household income. The activity was carried out by the Institut Teknologi Sawit Indonesia team consisting of lecturers and students together with partners, namely housewives in Batang Kuis Village, Deli Serdang, totaling 75 people. Activities were carried out in June 2024. The method implemented in this empowerment program is a participatory method starting from education and socialization, practical application of composting, and monitoring of fermentation results while stimulating partners to be able to process waste independently which has the opportunity to produce products of economic value to increase family income. The results of this service activity achieved a score of 97% because the team succeeded in educating partners and motivating them to process waste using the composting method and reduce the burning process or piling up garbage waiting for the janitor to pick up the garbage. This activity is expected to continue for partners by continuing to provide assistance to housewives in Batang Kuis Village so that it becomes a partner business unit to increase family income.